Behavioral Health Service Use by Military Children during Afghanistan and Iraq Wars - Wooten, Nikki R. (J Behav Health Serv Res, 2019)
Medical claims were analyzed from 2,810 military children who visited a civilian emergency department (ED) or hospital from 2000–2014 with behavioral health as the primary diagnosis and TRICARE as the primary/secondary payer. Visit prevalence was estimated annually and categorized: 2000–2002 (pre-deployment), 2003–2008 (first post-deployment), 2009–2014 (second post-deployment). Age was categorized: preschoolers (0–4 years), school-aged (5–11 years), adolescents (12–17 years). During Afghanistan and Iraq wars, 2,562 military children received 4,607 behavioral health visits. School-aged children’s mental health visits increased from 61 to 246 from pre-deployment to the second post-deployment period. Adolescents’ substance use disorder (SUD) visits increased almost 5-fold from pre-deployment to the first post-deployment period. Mental disorders had increased odds (OR=2.93, 95% CI: 1.86–4.61) of being treated during hospitalizations than in EDs. Adolescents had increased odds of SUD treatment in EDs (OR=2.92, 95% CI: 1.85–4.60) compared to hospitalizations. Implications for integrated behavioral health and school behavioral health interventions are discussed.